Ukraine - Review of the Budget Process : A Public Expenditure and Institutional Review - World Bank (Washington, DC, 2013)
This report is a companion report of the Country Financial Accountability Assessment. It presents an institutional analysis of the budget process, which is the process by which the government allocates funds to spending agencies. It analyzes the participants in the decision-making process related to spending and the institutions involved in the budgetary and financial management of government operations, as well as the modalities of preparation and execution of the budget. The report also updates the findings of the 1997 Public Expenditure Review concerning fiscal sustainability and the size and composition of public expenditure, which is discussed in an international context. Finally, the report provides recomendations on how to improve the management of public resources.